HISTOPATHOLOGICAL AND BIOCHEMICAL STUDIES ON THE EFFECT OF TRIGONELLA FOENUM GRAECUM AND COCCINIA INDICA EXTRACTS IN STREPTOZOTOCIN INDUCED DIABETIC RATS - SHESHA RAO; SUGUNA RAO; SHETTAR M (International Journal of Pharma and Bio Sciences, 2014)
The present study was taken up to evaluate the efficacy of Trigonella foenum graecum and Coccinia indica individualy and in combination in streptozotocin induced diabetic rats for a period of 90 days. The various groups in this study included normal control (Group-I), diabetic control (Group-II), diabetic rats treated with Trigonella foenum graecum (Group-III), diabetic rats treated with Coccinia indica (Group-IV), diabetic rats treated with Trigonella foenum graecum and Coccinia indica (Group-V) respectively. There was significant variation in biochemical and pathomorphological parameters of diabetic rats when compared to normal control rats. The alleviation of the diabetic and its complications induced by streptozotocin was observed in all the treatment groups with variable degree of improvement. Trigonella foenum graecum and Coccinia indica extracts were effective in alleviating streptozotocin induced diabetes. Combination of Trigonella foenum graecum and Coccinia indica showed better improvement compared to individual extract alone and improvement was statistically significant. However the combined treatment of Trigonella foenum graecum and Coccinia indica revealed a very good antidiabetic effect with reference to improvement in insulin level and beta cell number which indicated a synergistic effect between Trigonella foenum graecum and Coccinia indica